Analysis of the spatial distribution of dengue in the state of Piauí from 2015 to 2019 - da Silva Lemos, Matheus Henrique; Lopes Filho, Lauro Lourival; de Oliveira Costa, Maria Amélia; Salmito Cavalcante, Maria do Amparo; Campelo, Viriato; Sousa Júnior, Vicente de Paula (O Mundo da Saúde, 2022)
Dengue is an arboviral disease considered global public health challenge, as it provides lasting damage, thus representing a threat to human health. Therefore, this study aimed to analyze the spatial distribution of dengue cases in Piauí between 2015 and 2019. This was a spatial ecological study of dengue, with data from the Disease Notification Information System (SINAN) from 2015 to 2019. The X² association test was applied for the bivariate analysis and the Qgis software (version 3.16.7. Hannover) was used for spatial analysis. During this period, 27,289 cases and 21,944 confirmed cases of dengue were reported. The city of Teresina (62.9%) and the health region Entre Rios (65.84%) had the highest records. Females (58.4%), between 20 and 34 years old (33.52%) and mixed race (44%) were the most affected. As for education, 58.5% did not respond. Dengue cases are concentrated in poles with large population flows. The identification of the epidemiological profile, as well as its main risk factors, is a way to help the health system of the entire state to elaborate specific control policies for the population most vulnerable to the disease.